2018
DOI: 10.24114/jpkim.v10i3.12704
|View full text |Cite
|
Sign up to set email alerts
|

The difference of student’s activities and learning outcome with problem based learning using macromedia flash and handout

Abstract: This study aimed to determine the difference of student's activities and learning outcome with PBL using macromedia flash and handout. The sample were selected using purposive sampling into experimental group I and experimental group II with 60 students. The experimental group I used the PBL using macromedia flash, while the experimental group II used the PBL using handout. The results indica ted that the mean scores of student's activities and learning outcome in the experimental group II were significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Efforts to improve one's cognitive skills need to be supported by an increase in metacognitive skills. In its application in learning activities or problem solving, cognitive and metacognitive processes can take place simultaneously, which support each other (Yustina, 2012;Purba et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve one's cognitive skills need to be supported by an increase in metacognitive skills. In its application in learning activities or problem solving, cognitive and metacognitive processes can take place simultaneously, which support each other (Yustina, 2012;Purba et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This media is generally in the form of books or papers that can be studied and discussed by students after learning class. Purba et al (2018), reported that learning with the use of media handouts can improve students' learning outcomes and be higher than the learning outcomes of students who are taught using macromedia flash.…”
Section: Discussionmentioning
confidence: 99%
“…However, multimedia is not always more influential than conventional media such as handouts. Purba et al (2018), reports that student learning outcomes on the use of media handouts are higher than student learning outcomes in the use of macromedia flash. Media handouts can stimulate student curiosity so that there is an increase in learning activities that affect the increase in learning outcomes (Agustina et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A teacher's motivation can even influence the development of his students (Utomo et al 2019). In general, digital integrated learning methods can improve student learning outcomes (Purba et al 2018) and student motivation ).…”
Section: Introductionmentioning
confidence: 99%